PERANAN SATUAN POLISI LALU LINTAS DALAM MENANGANI PELANGGARAN KECEPATAN MELAMPAUI BATAS MENURUT UNDANG-UNDANG NOMOR 22 TAHUN 2009 TENTANG LALU LINTAS DAN ANGKUTAN JALAN DI KEPOLISIAN RESOR KOTA PEKANBARU - Ridho Triwardana; Erdianto '; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Each person uses a motor vehicle to facilitate its activities to mobilize or move from one place to another in everyday life, be it a two-wheeled vehicle or four wheels. Motor vehicle is any vehicle that is driven by mechanical equipment such as engines other than vehicles running on rails. As motorists must give priority to the safety and comply with the applicable regulations in accordance with the provisions in force in the State Indonesia. Pursuant to Article 106 paragraph (4) (g) or Section 115 (a) of Law Number 22 Year 2009 regarding Traffic and Road Transportation. The research objective of this thesis, namely; First, to determine the role of Pekanbaru City Traffic Police, Second, To know the constraints faced by the City Police Traffic Pekanbaru, Third, To know the efforts made by the City Police Traffic Pekanbaru.This type of research can be classified into types of juridical sociological research, because in this study the authors directly conduct research on location or area under study in order to provide a complete and clear picture of the problem under study. This research was conducted in the Unit and Traffic Police Pekanbaru, while the sample population is a whole party with regard to the issues examined in this study, the data source used, primary data, secondary data, and the data tertiary, data collection techniques in research This observation, interviews, questionnaires and studies literature.From the research, there are two basic problems that can be concluded. First Traffic Police Unit Pekanbaru City resort has an important role in addressing melalmpaui speed limit to foster and disseminate to the public of its speed exceeds the limit by reprimanding and sanctioning offenders if proved to have violated the speed limit exceeded. The second obstacle faced Traffic Police Unit resort city of Pekanbaru, among others, the absence of gauges or radar speed to prove offenders who violate the rules speed exceeds the limit, people who do not know the basis of the regulation speed exceeds the limit, and not maximal means of signs regulation speed on the national road in the city of Pekanbaru, the result of people who do not know about the speed regulation makes a lot of accidents that causes the speed beyond the limit, and the awareness that did not exist, but to actively participate in the creation of traffic orderly and safe.Keywords: Role - Traffic Unit - exceed speed limits